2000
DOI: 10.1071/as00056
|View full text |Cite
|
Sign up to set email alerts
|

The Optical/Near-IR Colours of Red Quasars

Abstract: Abstract:We present quasi-simultaneous multi-colour optical/near-IR photometry for 157 radio selected quasars, forming an unbiassed sub-sample of the Parkes Flat-Spectrum Sample. Data are also presented for 12 optically selected QSOs, drawn from the Large Bright QSO Survey. The spectral energy distributions of the radio-and optically-selected sources are quite different. The optically selected QSOs are all very similar: they have blue spectral energy distributions curving downwards at shorter wavelengths. Roug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 21 publications
11
92
0
Order By: Relevance
“…This detection rate of 36% suggests that the Ðnal 2MASS catalog will yield matches for approximately 4760 of the 13214 VV00 quasars. Our sample of 2277 quasars with IR data is nearly 10 times larger than the largest previous such sample (Srianand & Kembhavi 1997) and more than 10 times larger than the largest previous samples with homogeneous IR data (Warren et al 2000 ;Francis et al 2000).…”
Section: Selection On Optical and Near-infrared Colorsmentioning
confidence: 87%
See 3 more Smart Citations
“…This detection rate of 36% suggests that the Ðnal 2MASS catalog will yield matches for approximately 4760 of the 13214 VV00 quasars. Our sample of 2277 quasars with IR data is nearly 10 times larger than the largest previous such sample (Srianand & Kembhavi 1997) and more than 10 times larger than the largest previous samples with homogeneous IR data (Warren et al 2000 ;Francis et al 2000).…”
Section: Selection On Optical and Near-infrared Colorsmentioning
confidence: 87%
“…Dust obscuration seems the simplest explanation for Figure 4, although we note that Francis, Whiting, & Webster (2000) concluded that synchrotron emission was the best explanation for the red colors of the many RLQs in the Parkes Half-Jansky sample of Webster et al (1995).…”
Section: Catalog Cross-correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure sufficient flux against which to detect the absorption (Sect. 2.2), sources were selected from the Parkes Half-Jansky Flat-spectrum Sample (PHFS, Drinkwater et al 1997;Francis et al 2000), giving a total of ten targets with redshifts of z = 0.219 − 0.405. Lastly, the sources were prioritised by faintness, for which we chose B > ∼ 19 (as quoted in the PHFS, Table 1), since this gave the ten faintest targets for which the estimated flux density at the redshifted H I 21-cm absorption frequency, Sest, was confirmed to exceed 0.5 Jy.…”
Section: Sample Selectionmentioning
confidence: 99%